Mechanical Properties and Thermal Stability of Epoxy/RTV Silicone Rubber - Pakaya, Fahriadi; Ardhyananta, Hosta; Wicaksono, Sigit Tri (IPTEK The Journal for Technology and Science, 2017)
Epoxy products have been widely applied in industries such as in the fields of automotive, mechanical, electrical, and chemical engineering. Epoxy modified to be done to improve the mechanical properties, thermal stability, physics and chemical resistance. Using of other compounds as curing agents has long been commercialized, but the constraints posed is application of an epoxy thermoset on areas requiring impact strength and thermal stability are still low. One of the modification that has been done is addition of other material as the second material to improve properties of thermoset epoxy. Preparation of research material obtained through the provision of a second material that is RTV silicone rubber. The aim of research to analyze effect of RTV silicone rubber composition (0, 5, 10, 15, 20) wt% of the mechanical properties and thermal stability of thermoset epoxy. Testing and characterization conducted on thermoset epoxy by the addition of RTV silicone rubber. In addition RTV silicone rubber: tensile strength, elongation at break and hardness has decreased, energy and impact strength increased maximum on the addition of 15% RTV silicone rubber respectively 0.294 J and 6175 J / m2. The maximum degradation of temperature increase in the addition of 15% RTV silicone rubber is 328 and 349oC respectively at 5 and 10% degradation.